Teori ACTORS dalam Pemberdayaan Masyarakat - Maani, Karjuni Dt. (Pusat Kajian Civics Fakultas Ilmu-ilmu Sosial Universitas Negeri Padang, 2011)
By using the concept of empowerment that are offered within the framework of the theory of